THE REGIME SWITCHING OF CYCLE INSTABILITY OF ISLAMIC BANKING AND THE ECONOMY: EVIDENCE FROM INDONESIA, MALAYSIA, AND PAKISTAN - Nurfalah, Irfan; Rusydiana, Aam Slamet (Journal of Islamic Monetary Economics and Finance, 2021)
This study aims to examine the cyclical instability of Islamic banking in Indonesia, Malaysia, and Pakistan. A stable Islamic banking system can give the public confidence to conduct transactions and thus grow the economy. The proxy variable for stability used is the z-score, with 156 periods of research data from January 2007 to December 2019. The Markov Switching Vector Autoregression (MS-VAR) method was employed. The results show that Islamic banking stability in Indonesia based on the z-score is more stable than others. Nevertheless, in terms of the regression of all the variables, regime shifting, and the duration of the crisis, overall Malaysian Islamic banking displays the best performance. The instability of the Indonesian model is mostly affected by inflation, whereas Malaysia and Pakistan are affected by the financing to deposit ratio and the fluctuation in global oil, respectively.